A two‐tier conception of European Union peoplehood: A realist study of European citizens' bonds of collectivity. Issue 6 (21st February 2018) - Beetz, Jan Pieter
Abstract: The European Union (EU) struggles to legitimate its rule. This realist study develops a conception of peoplehood in the EU polity, because, in contemporary Europe, 'the people' remains the sole source of political legitimacy. From a realist perspective, a conception of peoplehood should yield a coherent story why EU citizens should accept, or at least acquiesce, to EU rule. This study explores the possibility of a pluralistic conception being either multi‐layered, multi‐faceted or both. Taking a practice‐dependent approach, I first analyse the institutional systems that structure relationships between EU citizens. I secondly propose conceptions of EU citizens' bonds of collectivity. Thirdly, I develop a novel two‐tier conception of EU peoplehood in which individuals remain bound together as national peoples, while these peoples are in turn united by commercial and liberal bonds. I submit that this conception can lay the foundation for a convincing story to legitimate EU rule.